Electron Reconnection in the Magnetopause Current Layer. Issue 11 (13th November 2018) - Norgren, C.; Graham, D. B.; Khotyaintsev, Yu. V.; André, M.; Vaivads, A.; Hesse, M.; Eriksson, E.; Lindqvist, P.‐A.; Lavraud, B.; Burch, J.; Fuselier, S.; Magnes, W.; et al.
Abstract: The electron dynamics within thin current sheets plays a key role both for the process of magnetic reconnection and other energy transfer mechanisms but, from an observational point of view, is not well understood. In this paper we report observations of a reconnecting current sheet with intermediate guide field B G =0.5 B in, where B in is the magnetic field amplitude in the inflow regions. The current sheet width is comparable to electron spatial scales. It shows a bifurcated structure and is embedded within the magnetopause current layer with thickness of several ion scales. The electron scale current sheet has strong out‐of‐plane and in‐plane currents, Hall electric and magnetic fields, a finite magnetic field component normal to the current sheet, and nongyrotropic electron distributions formed due to finite gyroradius effects at the boundary of the current sheet. Comparison between test particle simulations and electron data shows that electrons approaching from the edge of the largest magnetic curvature are scattered to perpendicular pitch angles in the center of the current sheet while electrons entering from the opposite side remain close to field aligned. The comparison also shows that an observed depletion in phase space at antiparallel pitch angles can be explained if an out‐of‐plane electric field, which due to the guide field is close to antiparallel to the magnetic field, is present in the center of the current sheet. This electric field would be consistent with the reconnection electric field, and we therefore interpret the depletion of electron phase space density as a manifestation of ongoing reconnection. Key Points: A reconnecting electron scale current sheet is observed inside a filamented magnetopause current layer Due to a guide magnetic field and related magnetic curvature, electrons entering from opposite sides have different behavior The presence of an out‐of‐plane electric field can explain observed electron distributions